Evaluation of Antibacterial Activity and Characterization of Phytochemical Compounds from Selected Mangrove Plants - M. Duraipandian; H. Abirami; K.S. Musthafa; S. Karuthapandian (International Journal of Biomedicine, 2022)
The aim of this study was to investigate the antibacterial activity of n-butanol, petroleum ether, ethyl acetate, ethanol, methanol, and chloroform extracts of the sponges and leaves of different mangrove species (Bruguiera cylindrica, Suaeda maritima, Ceriops decandra, Avicennia officinalis, Rhizophora apiculata, Suaeda monoica, Avicennia marina, and Rhizohora mucronata) against Proteus mirabilis ATCC 7002. Methods and Results: Agar well diffusion method was used to evaluate the antimicrobial activity of selected mangrove extracts. The active compounds from mangrove sponges and leaves with various solvents were examined under Fourier transform infrared (FTIR) spectroscopy. The ethyl acetate extracts, methanol extracts, chloroform extracts, n-butanol extracts, and petroleum ether extracts of selected mangrove leaves (B. cylindrical, S. maritime, A. officinalis, S. monoica, A. marina, R. mucronata) showed good antibacterial activity against P. mirabilis ATCC 7002. FTIR analysis of crude methanol extract of S. monoica showed the presence of amide and alkane groups in phytochemicals. For crude methanol extract of R. mucronata, the presence of phenol, nitro, amide, and alkane groups was revealed. Conclusion: the results obtained revealed industrially important mangrove extracts and the functional groups of plant compounds responsible for great antibacterial activity.